Relationship between fibrinogen level and advanced colorectal adenoma among inpatients: A retrospective case-control study - Wang, Huijie; Zheng, Huanwei; Cao, Xu; Meng, Ping; Liu, Jinli; Wang, Zhichao; Zhang, Teng; Zuo, Haiying (Frontiers in Medicine, 2023)
Objective This study was to explore the relationship between fibrinogen and advanced colorectal adenoma among inpatients. Methods From April 2015 to June 2022, 3738 participants (566 case subjects and 3172 control subjects) who underwent colonoscopies enrolled, and smooth curve fitting and logistic regression models were applied to explore the association between fibrinogen and advanced colorectal adenoma. In addition, sensitivity and subgroup analyses were performed to assess the stability of the results. Results Compared with lower fibrinogen quantile 1 (< 2.4 g/L), the adjusted OR values for fibrinogen and advanced colorectal adenoma in quantile 2 (2.4–2.75 g/L), quantile 3 (2.76–3.15 g/L), and quantile 4 (≥3.16 g/L) were 1.03 (95% confidence interval [CI]: 0.76–1.41), 1.37 (95% CI: 1.01–1.85), and 1.43 (95% CI: 1.06–1.94), respectively. A linear relationship between fibrinogen and advanced colorectal adenoma was observed. Sensitivity and subgroup analyses showed stable results. Conclusion Complements the evidence that fibrinogen was positively associated with advanced adenomas, suggesting that fibrinogen may play a role in the adenoma-carcinoma sequence.